Comparative Study on the Social Psychology of Designed and Un-designed University Campus - Anik, Mohammad Rakibul Islam; Zohora, Fatema Tuz; Basure, Ashefa Washema; Rahman, Iftekhar (South Asian Journal of Social Sciences and Humanities, 2025)
This comparative Study on the Social Psychology of Designed and Undesigned Campuses  examines how a campus's intentionally or unintentionally designed landscape components  influence students’ psychological impacts, attendance and social interactions. It is conducted  by a designed online questionnaire based on the components of landscape desirability and  students’ mental health responses to that such as understanding, exploration, compatibility with  the desire for participation, and depression and anxiety. The questionnaire was given to a total  of 100 university students. The sampling method was random clustering based on public and  private university categories. The data from the questionnaire was analyzed using statistical  methods and comparison techniques. The ultimate goal is to compare and prioritize the  desirability factors of the designed landscape on campuses, and the student's attendance at the  university which can assist universities in creating environments that promote positive  student experiences, reduce mental health issues, and increase attendance and social  involvement. This study can inform future campus development, enhancing the entire  educational experience and promoting student achievement through well-designed spaces.
Keywords: Campus design; Psychological impacts; Landscape desirability; Mental health; Green spaces; Social psychology; Emotions and behaviour